The Drivers of Team-based Inside Sales Performance at Different Stages of the Sales Pipeline. - Haque, Rahat (Université d'Ottawa / University of Ottawa, 2019)
There is a lack of academic research on sales teams, despite team selling becoming more prominent in recent years. Particularly in Inside Sales, there is a lack of clarity as to what are the drivers of optimum team-based selling and their degree of effect on sales performance. We utilize a team-based approach that aims to study the characteristics of Inside Sales teams and their interactions with business leads, using data from a well-reputed leads management software vendor. Based on prior team-based constructs in the literature, we built a framework that posits Quality of Team Composition, Task Utility and Intra-team Coordination leading to different categories of sales performance at various stages of the sales pipeline via their reflective variables. We tested our conceptual model in the following fashion: first, we used text mining on sales results to classify the different stages of the sales pipeline. Following that, we measured the conversion ratio at each stage as appropriate. Next, we discretized each conversion ratio into three levels of performance groups. The outcome variables in the model are different categories of team performance at each stage of the sales pipeline. Subsequently, we used multinomial logistic regression to regress our outcome variables on our team-based predictor variables in the hopes of establishing and validating important drivers for nuanced Inside Sales success. We uncovered new insight regarding team-selling best practices, using pre-identified constructs from the literature which are uniquely suited to teams and also constructs which are aggregated at a team level from an individual level. Our study is especially relevant to the Inside Sales process, as the outcome measures relate to the sales pipeline. Our main finding was that in there is a difference in skills required at different stages of the sales pipeline, in that more customization and experience is needed at the more advanced stages, whereas more repetition of activity is needed at the beginner stages. We also found that smaller team sizes tend to do better in Inside Sales, which was an unsettled research question in team research with plenty of evidence in favor of both smaller and bigger teams. Additionally, even if it was not a primary goal of our study, by virtue of classifying the leads by their final outcomes, we stumbled across an interesting finding, which is that an overwhelming majority of the sales leads tend to stay at one stage in their entire lifecycle. The implications of all our findings are very relevant to both practitioners and researchers of Inside Sales who are interested in team-based sales optimization. More research should be done in the field of Industrial Marketing, building upon what we found to be true for the B2B sector.
Keywords: Inside Sales; Marketing Strategy; Sales Pipeline; Team Performance; Business Leads; Team-based Selling